A efetividade do Programa de Bolsa de Inovação Tecnológica de Roraima – BITERR - Missio, Graciela (2019)
The capacity for innovation in companies can be intensified as a stimulus for technology transfer between universities and companies. With the intention of broadening and fostering this approach of the actors, programs for fostering innovation have emerged that seek to implement research and development (P&D) activities in companies with the help of universities. This joint work assists in the evolution of the corporate culture, where the innovations generated can become a reality implemented. In this format, undertand the effectiveness the Roraima Technological Innovation Scholarship Program, BITERR, for the participating companies, in the implementation of innovation projects and the results generated for the companies is the objective of this researtch. The objective was to evaluate the actual implementation of the innovations generated during four program cycles, which factors were positive, which barriers were found and to know the main results obtained during the program performance. Then were evaluated companies three winning projects of each cycle, from different areas of expertise, participating in BITERR between 2015 and 2018, were evaluated, totaling 12 projects. The results demonstrated by the research show that the projects have a very consistente degree of implementation, demonstrating that process improvement was a very significant result for the program and that the barriers found in the execution and implementation are related to human resources and technical capacity of the team. The information obtained by this research will serve as basis for the institutions that perform the BITERR can make strategic decisions with corrective actions and /or new paths to the program.